METHODOLOGY OF TEACHING INFORMATICS IN ELEMENTARY GRADES - Ergasheva Khilolokhan Muydinjonovna (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the methodology of teaching computer science in primary grades, the integration of computer science in the curriculum, project-based learning, involving students in practical, project-based learning experiences, their creativity, critical thinking and collaboration. It was discussed about the development of skills. This article aims to explore research-based strategies and methodologies for teaching computer science in elementary grades.